BILL S-231: The Ethics of Familial and Genetic Genealogical Searching in Criminal Investigations - Clausius, Katharina; Kenny, Erin; Crawford, Michael (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Recent breakthroughs in criminal investigations, especially of high-profile cold cases, have helped to consolidate the role of DNA analysis in investigative contexts. Consequently, some jurisdictions are looking to expand DNA collection and analysis methods. In Canada, legislation has been proposed to expand the National DNA Databank (NDDB) and to allow familial searching in criminal and forensic investigations. This article outlines the ethical implications of the proposed legislation and, more broadly, of genealogical methods already in use that operate outside the NDDB and rely heavily on for-profit and consumer DNA services. Current DNA analysis within the criminal justice system is heavily regulated and provides important protections not only for individuals but also for genetic relatives whose biometric data is indirectly implicated. In contrast, familial searching poses risks for offender privacy as well as for their relatives. Additionally, the expanding practice of genetic genealogical searching relies on unregulated commercial products that use different technology to expose highly detailed genetic information. This technology falls short of rigorous investigational standards and poses significant problems for informed consent. We conclude that expanding DNA collection within the NDDB to include familial searching risks exacerbating existing systemic bias and that genetic genealogical searching outside of the NDDB is incompatible with existing Canadian legislation that safeguards privacy, genetic non-discrimination, and fundamental rights and freedoms.